2006
DOI: 10.1007/s11431-006-2005-2
|View full text |Cite
|
Sign up to set email alerts
|

Study on design pressure of in-service welding pipes

Abstract: A method of predicting design pressure and burn-through of in-service welding pipes was established. Temperature distributions of in-service welding under variable parameters were simulated by FEM. The effect of flowing of internal media was regarded as forced convection. Based on the numerical results, design pressure of the pipe can be obtained and burn-through can be predicted. It can be concluded that the design pressure decreases with the increasing of heat input. RSF and design pressure of the pipe incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 4 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…Thus, it is necessary to consider the influence of the characteristics of the internal flow on the safety of welding in operation. Xue et al [11] suggests that if the fluid has low viscosity and convection is forced, the number of Nusselt (Nu) can be calculated by Equation 5: in which Pr is the Prandtl number, h [W.m -2 . K -1 ] is the coefficient of forced convection and k f [W.m -1 .K -1 ] is the thermal conductivity of the fluid.…”
Section: Thermal Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is necessary to consider the influence of the characteristics of the internal flow on the safety of welding in operation. Xue et al [11] suggests that if the fluid has low viscosity and convection is forced, the number of Nusselt (Nu) can be calculated by Equation 5: in which Pr is the Prandtl number, h [W.m -2 . K -1 ] is the coefficient of forced convection and k f [W.m -1 .K -1 ] is the thermal conductivity of the fluid.…”
Section: Thermal Analysismentioning
confidence: 99%
“…A new mathematical description of the heat source for welding with manual coated electrode was introduced into his work, but limited data were provided for the temperature profiles. Xue et al [11] established a method to predict the rupture pressure and strain in operation under variable parameters using FEM. It has been shown that the rupture pressure of the project decreases when amount of heat input increases.…”
Section: Introductionmentioning
confidence: 99%